Assess the hearing of contralateral ear in patients with unilateral chronic squamosal otitis media - Khan, Raphella; Kasliwal, Anirudh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic squamosal otitis media can occur due to many conditions affecting the middle ear. Most common sign of developing a chronic squamosal otitis media is formation of a retraction pocket in the tympanic membrane leading to further development of a cholesteatoma and if not treated properly, may lead to development of dangerous complication in the affected ear. These etiological factors may also affect the other ear. It is therefore very necessary to assess and diagnose the contralateral ear, so that the disease can be intervened and treated at the right time, to prevent any deterioration in hearing of the contralateral ear. Methods: The prospective study was done in 100 patients with unilateral chronic squamosal otitis media, where the contra lateral ear was examined and assessed for any hearing loss. Results: We found hearing loss in the contra lateral ear ranging from mild conductive hearing loss to sensorineural hearing loss with the maximum patients with mild conductive hearing loss (42%) and lowest in sensorineural hearing loss (1%). Conclusions: In our study, 76 patients were seen with conductive hearing loss. Out of that, 42% patients were seen with mild conductive hearing loss, 30% with moderate conductive hearing loss and 4% with severe conductive hearing loss. 20% patients were seen with normal hearing. 3% patients were seen with mixed hearing loss and only 1% patient was seen with sensorineural hearing loss in contralateral ear.